Morphometry of nasopalatine line for transnasal endoscopic access to craniovertebral junction: A cadaveric study - D Bharathi; Deepali Deshatty; B N Shruthi (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Lesions in craniovertebral junction (CVJ) are approached either through transnasal or transoral route. Endoscopic transnasal route reduces significant morbidity, and nasopalatine line (NPL) predicts the inferior-most limit of surgical dissection. The purpose of the present study was to measure the NPL in the cadavers, which is beneficial for the endoscopic transnasal anterior approach to access odontoid process and anterior CVJ, especially in surgical decompression of medulla oblongata. Materials and Methods: The present study was done on forty midline sagittal head-and-neck specimens obtained from 10% formalin-fixed cadavers in the Department of Anatomy, Rajarajeswari Medical College and Hospital, Bangalore. Using slide calipers, the hard palate line (HPL), which extends from the anterior nasal spine of maxillary bone to the posterior nasal spine of palatine bone and NPL which extends from the inferior-most point of nasal bone to the posterior nasal spine were measured. In addition, HPL was extended to the lower limit of the anterior margin of the foramen magnum, and NPL was further extended posteriorly to the ventral surface of the second cervical vertebra to know the inferior limit of transnasal endoscopic access for surgeries on ventral skull base lesions. Results: The average of HPL and its extension to foramen magnum was found to be 45.83 mm and 40.97 mm respectively. The NPL and its extension to the ventral surface of C2 vertebra were found to be 58.22 mm and 37.18 mm, respectively. Conclusion: HPL & NPL provide useful information for the neurosurgeons to access the lesions in the ventral CVJ and to achieve a good outcome.